2013
DOI: 10.1097/mnh.0b013e32835a17ae
|View full text |Cite
|
Sign up to set email alerts
|

Sodium glucose cotransporter 2 and the diabetic kidney

Abstract: The available clinical evidence shows consistent reduction in glycaemic parameters and some evidence suggests additional effects including weight loss and mild blood pressure reduction. There are some side effects that warrant further investigation and establishing whether SGLT2 inhibition provides a renal benefit relies on future long-term studies with specific renal end-points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 46 publications
0
46
0
3
Order By: Relevance
“…Interestingly, SGLT2 inhibitors also have renal hemodynamic effects, including reducing glomerular hyperfiltration (11), as well as inhibitory effects on the inflammatory and fibrotic responses of proximal tubular cells to hyperglycemia (12). The SGLT2 is localized to the proximal tubule and is responsible for ;90% of the reabsorption of the glucose filtered by the kidney.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, SGLT2 inhibitors also have renal hemodynamic effects, including reducing glomerular hyperfiltration (11), as well as inhibitory effects on the inflammatory and fibrotic responses of proximal tubular cells to hyperglycemia (12). The SGLT2 is localized to the proximal tubule and is responsible for ;90% of the reabsorption of the glucose filtered by the kidney.…”
mentioning
confidence: 99%
“…Several review articles, primarily in nephrological journals (11,12,(17)(18)(19)(20), have considered the potential nephroprotective effects of SGLT2 inhibitors. The present review will emphasize considerations for the diabetologist, especially in discussion of the use and limitations of SGLT2 inhibitors in improving glucose control in patients with chronic kidney disease (CKD).…”
mentioning
confidence: 99%
“…Animal studies have demonstrated that SGLT2 inhibitors decrease glomerular inflammation and fibrosis, and reduce albuminuria. 32 The results of an extension of the EMPA-REG OUTCOME trial demonstrated that empagliflozin had favourable renal outcomes in patients with severe renal impairment and diabetes, and this could encourage broader use of such drugs in patients with diabetic nephropathy in the future. 34 The most common side-effects of SGLT2 inhibitors are polyuria and increased risk of bacterial and fungal genitourinary infections.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…They act by reducing glucose and sodium reabsorption in the proximal tubule, causing tubuloglomerular feedback, afferent arteriole vasoconstriction and reduction in hyperfiltration. 32,33 In patients with type 2 diabetes, they give rise to a transient reduction in eGFR. Animal studies have demonstrated that SGLT2 inhibitors decrease glomerular inflammation and fibrosis, and reduce albuminuria.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…Adenosine triggers vasoconstriction of the afferent arteriole with reduction of intraglomerular pressure [49][50][51]. In addition, reduced glucose passage across the proximal tubular cells may lead to decreased oxidative stress, inflammation, and tubuleinterstitial fibrosis [52].…”
Section: Dapagliflozin In Special Populationsmentioning
confidence: 99%